Analisis Kelayakan Investasi Pendirian Usaha Jasa Penggilingan Daging di Kabupaten Jember – Jawa Timur - Heri Istanto; Isti Fadah; Hadi Paramu (RELASI : JURNAL EKONOMI, 2016)
Every investor or businesses expect the investments made will benefit in the long term. However, often such investment activity are faced with various problems. One of them is the problem of the financial aspects. Financial aspects are basically related to funding issues and issues cash refund long and uncertain. Therefore, before taking the decision to invest, one important requirement is to conduct a feasibility study of the financial aspects (financial) using several methods of analysis. NPV method produces a value of Rp80.206,00, DPP method is obtained payback period of 4 years and 4 months 5 days, methods IRR obtained a value of 32.05%, MIRR method values obtained 32.03% and Monte Carlo simulation 500 times produce Rp48.358.585,00 average value, standard deviation of Rp46.531.556,00 and P (NPV <0) of 14.93%. Based on the results of a calculation by the method of NPV, IRR, MIRR and Monte Carlo Simulation, investment services business establishment grinding meat in Jember feasible. While the analysis of the DPP method, the investment is not feasible.